2020
DOI: 10.1002/pbc.28515
|View full text |Cite
|
Sign up to set email alerts
|

Management of methotrexate‐induced neurotoxicity with aminophylline plus dextromethorphan in a pediatric patient with pineoblastoma

Abstract: Methotrexate (MTX)-induced neurotoxicity is a serious adverse event associated with potentially deleterious neurological manifestations. 1-10 Proposed management of MTX-induced neurotoxicity includes supportive care, leucovorin, dextromethorphan, and aminophylline. 1,2,8-13 Dextromethorphan is a noncompetitive N-methyl-D-aspartate receptor antagonist that has been reported as a potential treatment modality at antitussive doses of 1-2 mg/kg (maximum 60 mg/dose) by mouth twice daily; however, dextromethorphan us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…5 Thus, aminophylline is used for the treatment of methotrexate-induced neurotoxicity caused by an increase in adenosine levels, which seems to act by the blockade of adenosine receptors. 3,[5][6][7][8] Liao et al 1 used high-dose aminophylline (12 mg/kg for 6 consecutive days) to treat methotrexate-induced neurotoxicity in B-cell lymphoma with brain metastasis. However, the following points should be considered regarding the dosage of aminophylline to be used for the treatment of methotrexate-induced neurotoxicity.…”
Section: Dosage Of Aminophylline Used For the Treatment Of Neurotoxic...mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Thus, aminophylline is used for the treatment of methotrexate-induced neurotoxicity caused by an increase in adenosine levels, which seems to act by the blockade of adenosine receptors. 3,[5][6][7][8] Liao et al 1 used high-dose aminophylline (12 mg/kg for 6 consecutive days) to treat methotrexate-induced neurotoxicity in B-cell lymphoma with brain metastasis. However, the following points should be considered regarding the dosage of aminophylline to be used for the treatment of methotrexate-induced neurotoxicity.…”
Section: Dosage Of Aminophylline Used For the Treatment Of Neurotoxic...mentioning
confidence: 99%
“…The dosage of aminophylline described in previous reports that used aminophylline for the treatment of methotrexate-induced neurotoxicity in chemotherapy for acute lymphoblastic leukemia and pineoblastoma, was 2.5 mg/kg or 145 mg; this is relatively lower compared with the dosage described in this case report (12 mg/kg). 1,3,7,8 In addition, other case reports have suggested that intravenous aminophylline (100 mg every 6 hours) used for the treatment of methotrexate-induced neurotoxicity improved the symptoms. 6 However, treatment using aminophylline was ceased because of tachycardia and agitation as side effects of theophylline overdoses.…”
mentioning
confidence: 99%